REPRESENTATION OF THE MEANING AND MORAL MESSEGE OF THESONG LYRICS THE ALBUM WORLD, LOVE AND DIRT WORKS OF NADIN AMIZAH - Indiati, Fitri; Sasongko, Sempu Dwi; Sujarwoko, Sujarwoko (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2025)
Music is popular entertainment in the world because it can comfort the feelings of every listener. Therefore, music is widely used in various activities an professions. The big influence of music today is that Gen-Z imitates the lifestyle of their idols. This research aims to determine the representation of the meaning and moral message of the lyrics of the song “Rayuan Perempuan Gila. Semua Aku Dirayakan. And Tawa.” The method used is qualitative research using a content analysis technique approach. Then the study was carried out using Roland Barthes semiotic theory to find the meaning of song lyrics and Nurgiyantoro’s theory to find the moral message. The conclusion obtained from this research is the spirit of improving oneself after going through the storm of trauma and toxic relathinship in the past. A from of Gratitude is finding new people who always celebrate all events. Learn to self-love and be responsible for yourself